THORACOLUMBAR JUNCTION INJURIES AND THEIR MANAGEMENT WITH PEDICLE SCREWS - Khan, Inayatullah; Nadeem, Muhammad; Rabbani, Zia Hassan (Journal of Ayub Medical College Abbottabad, 2007)
Background: To evaluate the use of pedicle screw fixation in earthquake injured thoracolumbar spine. Methods: Nineteen patients with posttraumatic instability of lower thoracic or upper lumbar spine were included in the study. White and Panjabi criteriawas used to assess spinal instability. All patients underwent open reduction and internal fixation by posterior approach. Pedicles were localized using detailed anatomical landmarks and intraoperative imaging. . Local bone was used as bone graft. The neurological status of the patients and any other complications were noted up to one year. Results: There were 19 patients with unstable thoracolumbar junction injuries who were managed with pedicle screws and rods. Females were more affected (F:M ratio was 8.5:1). Wedge compression was the commonest. None of the patients deteriorated after surgery. There were 20 Frankel improvements in 18 patients (1.11 Frankel on average) with neurological deficit whereas 1 patient in Frankel E remained in the same grade on subsequent follow-ups. There was one patient with wound infection and one patient developed DVT. None of the patients developed bedsores. Conclusion: Pedicle screw fixation is a useful choice for thoracolumbar junction injuries for achieving reduction and stability in both anterior and posterior column injuries, without affecting extra motion segments. Keywords: Pedicle screws, thoracolumbar junction injuries